A Quantitative Electroencephalography Study on Cochlear Implant-Induced Cortical Changes in Single-Sided Deafness with Tinnitus - Song, Jae-Jin; Kim, Kyungsoo; Sunwoo, Woongsang; Mertens, Griet; Van de Heyning, Paul; De Ridder, Dirk; Vanneste, Sven; Lee, Sang-Youp; Park, Kyung-Joon; Choi, Hongsoo; Choi, Ji-Woong (Frontiers in Human Neuroscience, 2017)
The mechanism of tinnitus suppression after cochlear implantation (CI) in single-sided deafness (SSD) is not fully understood. In this regard, by comparing pre- and post-CI quantitative electroencephalography (qEEG), we explored cortical changes relevant to tinnitus improvement. In SSD patients who underwent CI, qEEG data was collected: 1) before CI, 2) 6 months postoperatively with CI-on, and 3) 30 minutes after CI-off and source-localized cortical activity/functional connectivity analyses were performed. Compared to the preoperative baseline, the CI-on condition demonstrated significantly decreased activity in the right auditory- and orbitofrontal cortices (OFC) for the delta frequency band as well as decreased connectivity between the auditory cortex/posterior cingulate cortex for the delta/beta2 bands. Meanwhile, compared to the CI-off condition, the CI-on condition displayed decreased activity in the right auditory cortices/OFC for the delta band, and in bilateral auditory cortices, left inferior frontal cortex/OFC for the gamma band. However, qEEG analyses showed no significant differences between the CI-off and baseline conditions. CI induced overall decreased cortical activity and functional connectivity. However, judging from no differences between the CI-off and baseline conditions, CI-induced cortical activity and functional connectivity changes are not by cortical plastic changes, but by dynamic peripheral reafferentation.